The songs of the revolution [videorecording] - Medina, Susan Calo.; GMA 7 (Television station : Quezon City).; National Commission for Culture and the Arts.; Travel Time (Television program). (Manila Travel Time, 1996)
Presents songs that advocates nationalism.
Mi Ultimo Adios / lyrics by Jose Rizal, music by Joey Ayala -- Alin mang lahi / words and music by Jose Rizal -- Ang martir / Anonymous -- Neneng sa iyo ang dahil / Anonymous -- Nang mauso ang damit kundiman / Anonymous -- Alerta Katipunan / Anonymous -- Doselyang Baliuag / Anonymous -- Parangal na dalit ng katagalugan / Julio Nakpil -- Pambansang Awit ng Pilipinas.
Documentary.
VHS.
Keywords: Revolutionary ballads and songs, Philippine